2013
DOI: 10.1017/s0954102013000679
|View full text |Cite
|
Sign up to set email alerts
|

Katabatic winds and polynya dynamics at Coats Land, Antarctica

Abstract: Abstract:Mesoscale model simulations were conducted for the Weddell Sea region for the autumn and winter periods of 2008 using a high-resolution, limited-area, non-hydrostatic atmospheric model. A sea ice-ocean model was run with enhanced horizontal resolution and high-resolution forcing data of the atmospheric model. Daily passive thermal and microwave satellite data was used to derive the polynya area in the Weddell Sea region. The focus of the study is on the formation of polynyas in the coastal region of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
5
23
0
Order By: Relevance
“…The regional‐scale COnsortium for Small‐scale MOdeling (COSMO) model (Rockel et al, ) is an RCM which has been applied over several regions of the world at different spatial and temporal resolutions. Its operation over the AIS is mainly limited to a few simulations in numerical weather prediction mode, studying individual snowfall events (Wacker et al, ) or polynya occurrence (Ebner et al, ; Haid et al, ). Some simulations with COSMO have been executed over polar regions (Gutjahr et al, ; Zhou et al, ), but these are mainly restricted to very short periods or studies of specific atmospheric phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The regional‐scale COnsortium for Small‐scale MOdeling (COSMO) model (Rockel et al, ) is an RCM which has been applied over several regions of the world at different spatial and temporal resolutions. Its operation over the AIS is mainly limited to a few simulations in numerical weather prediction mode, studying individual snowfall events (Wacker et al, ) or polynya occurrence (Ebner et al, ; Haid et al, ). Some simulations with COSMO have been executed over polar regions (Gutjahr et al, ; Zhou et al, ), but these are mainly restricted to very short periods or studies of specific atmospheric phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…For approximately 40 years, various studies showed that remote sensing approaches using passive microwave and thermal infrared data have proven to be valuable tools for this task. The resulting data can be utilized for verifying or augmenting (regional) climate and ocean models (Ebner et al, , ; Gutjahr et al, ; Sansiviero et al, , among others).…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of SPP 1158 mesoscale model simulations were conducted for the Weddell Sea using a highresolution (5 km) limited-area non-hydrostatic atmospheric model (Ebner et al 2014). In addition, a sea-ice/ocean model with enhanced horizontal resolution (3 km) was forced with the high-resolution data of the atmospheric model (Haid et al 2015).…”
Section: Katabatic Wind and Polynyasmentioning
confidence: 99%
“…The downslope surface offshore wind component of Coats Land is mainly steered by a pressure gradient due to katabatic force. Interestingly, the superimposed synoptic pressure gradient is opposed to the katabatic force during major katabatic wind events (Ebner et al 2014).…”
Section: Katabatic Wind and Polynyasmentioning
confidence: 99%